Analisis Pengaruh Faktor Meteorologi Terhadap Konsentrasi Gas SO2 dan NO2 dari Cerobong Ketel Pabrik Gula X: Analysis of the Influence of Meteorological Factors on SO2 and NO2 Gas Concentrations from the Boiler Chimney of Sugar Factory - Fifianah, Mareta; Amalia, Aussie (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The process of burning bagasse in a steam boiler produces pollutants in the form of exhaust gas emissions through the chimney, which can pollute air quality and harm health. The aim of this study is to determine the great influence of meteorological factors including exhaust gas temperature, air temperature, and flow speed in 4 areas of the boiler pipe that can affect the load of SO2 and NO2 gas pollutants through statistical data analysis. The ANOVA test used in this study was the ANOVA One Way test. The results of the study showed that there was a significant influence of the air temperature factor on SO2 in Boiler 4 / Cheng Chen with a value of F value 14,553 and a sig value of 0,032, as well as the influence that exists on the exhaust gas temperature factor and air temperature on NO2 in Stork Boiler 2 with an F value of 15,358 ; 17,889 and a sig value of 0.030 ; 0.024. The results of the analysis can be used as monitoring to evaluate the success rate and operational efficiency of the boiler under the management that has been carried out.